Effectiveness of individualized rTMS under sMRI guidance in reducing depressive symptoms and suicidal ideation in adolescents with depressive disorders: an open-label study - Sun, Yuyong; Liu, Xiaoyan; Li, Yi; Zhi, Qianna; Xia, Yong (Frontiers in Psychiatry, 2024)
BackgroundMajor Depressive Disorder (MDD) is occurring at a progressively younger age, and suicide is now the second leading cause of death among adolescents with MDD. Studies have shown that structural magnetic resonance imaging (sMRI) can improve the positioning accuracy and anti-depressant effects of repetitive transcranial magnetic stimulation (rTMS), thereby reducing suicidal ideation.ObjectiveTo compare the efficacy of sMRI-guided rTMS combined with pharmacotherapy, surface 5-cm rTMS positioning combined with pharmacotherapy, and pharmacotherapy alone on reducing depressive symptoms and suicidal ideation (SI) in MDD adolescents.MethodsThis was an open-label study of adjustable-dose pharmacotherapy combined with rTMS for the treatment of depressive symptoms and suicidal ideation in MDD adolescents. The three study groups were as follows: sMRI navigation for individualized rTMS coordinates targeting the dorsolateral prefrontal cortex (DLPFC) and in combination with pharmacotherapy for 10 rTMS sessions over two weeks; surface 5-cm positioning for DLPFC in combination with pharmacotherapy for 10 rTMS sessions over two weeks; pharmacotherapy. All patients received only one type of SSRIs anti-depressant. A total of 123 Chinese adolescents aged 13-18 with MDD were enrolled, and psychological parameters were evaluated in the first and second weeks of treatment.ResultsFollowing treatment, the clinical symptoms improved in all three groups. The sMRI navigation group exhibited significantly more improvement in depressive symptoms and suicidal ideation, without severe adverse reactions.ConclusionTen sessions of rTMS treatment are feasible and effective in improving depressive symptoms and reducing SI in MDD adolescents. The combination of sMRI navigation rTMS and pharmacotherapy was found to yield the best outcomes.Clinical trial registrationhttps://www.medicalresearch.org.cn/index, identifier MR-33-24-030536.